LUNG CANCER ASSOCIATED WITH CARBON BLACK EXPOSURE ON BRICK WORKERS - Anna nasriawati; Muhammad Ilyas; Indah S Widyahening (The Indonesian Journal of Public Health, 2021)
ABSTRACTCarbon black aerosol has potential risks to human health. It has been acknowledged to cause cardiovascular and respiratory diseases in humans. International Agency for Research on Cancer (IARC) 2010 stated that carbon black classification is 2b, which is carcinogenic. This research explains a case of lung cancer due to carbon black exposure and reviews the literature of occupational cases to get the answers about the effects of carbon black exposure and the increasing risk of lung cancer for workers exposed to carbon black. The literature review was performed to answer the clinical question via electronic databases: PubMed and Google Scholar. The keywords used were ‘carbon black’ and ‘lung cancer’ and 'workers'. The inclusion criteria of this searching strategy were the workers which exposed to carbon black, meta-analysis, randomized controlled trial, systematic reviews, cohort. The exclusion criteria of this article were inaccessible articles, RCTs that have been used in the recent systematic reviews. The selected articles were then critically appraised using relevant criteria by the Oxford Center for Evidence-based Medicine. This study reviews the literature by Rota Matteo; The epidemiological evidence on the polyaromatic hydrocarbon (PAH) high exposed, perspective cohort study by Delli LD, and the control case study by Marie EPt. All the researches above showed that carbon black carcinogenic potential is the same as the IARC monograph statement that the epidemiological studies of carbon black provide possible carcinogenicity (Group of 2B). Keywords: carbon black, lung cancer, workers